Resolution of the types and type localities of some early nominal species of the Australian myobatrachid frog genus Pseudophryne Fitzinger, 1843 - Shea, Glenn M.; Rowley, Jodi J.l. (Zootaxa, 2018)
The types and type localities of Bombinator australis Gray, 1835, Pseudophryne bibronii Günther, 1859, and Phryniscus albifrons Duméril, Bibron & Duméril, 1854, are defined. The nominal type locality for B. australis, Swan River, is considered to be in error. The source of the specimen, Joseph Wright, owned property in the Swan River colony in Western Australia, but later resided in Sydney, the latter locality within the known range of the species. We designate a specimen in the Museum National d’Histoire Naturelle, Paris as lectotype of Pseudophryne bibronii, restricting the type locality of both species to Parramatta, near Sydney, based on the published statements of the collector, François Péron. The holotype of Phryniscus albifrons, a species defined by a painting of a specimen, was likely to have been collected by Jules Verreaux, but the only extant Pseudophryne obtained from Verreaux does not match the type illustration. Verreaux is renowned for the numerous errors in the localities associated with his specimens, and the locality for this specimen, Moreton Bay, Queensland, is likely to be another such error. Resolution of these issues facilitates ongoing taxonomic work on the genus using genetic and morphological data.